Surface modification of La/SnO2–TiO2 nanocomposite via changing the ionic nature of surfactants. (7th September 2018) - Farrukh, Muhammad Akhyar; Muneer, Iqra; Sharif, Sidra; Munawar, Zeeshan; Batool, Nuzhat
Abstract: Surface of La/SnO2 –TiO2 nanocomposite was modified during its synthesis using zwitterionic (3 (N-N dimethyloctadecyl ammonia) propane sulfonate), anionic (sodium dioctyl sulfosuccinate) and cationic (dimethyl dioctadecyl ammonium chloride) surfactants by sol gel method followed by reflux method. Effect of surfactants on morphology was investigated with scanning electron microscopy. Crystallite size was determined by using XRD pattern with the help of Scherrer and Williamson Hall equations, while particle size was calculated through transmission electron microscopy. Optical properties as well as photocatalytic activity was investigated against degradation of methylene blue under sun light. It was found that doping of lanthanum enhanced the photocatalytic activity of SnO2 –TiO2 nanoparticles. A direct relation between particle size and band gap was found while both have inverse relationship with degradation and lattice strain.